Glycoprotein IIb/IIIa Blockade Inhibits Platelet-mediated Force Development and Reduces Gel Elastic Modulus - Carr, Marcus E, Jr; Carr, Sheryl L; Hantgan, Roy R; Braaten, Julie (Thrombosis and Haemostasis, 1995)
The effects of GPIIb/IIIa blockade on clot retraction were studied utilizing an instrument which directly measures force produced by platelets. GPIIb/IIIa disruption by calcium chelation, and GPIIb/IIIa blockade by peptides and anti-GPIIb/IIIa antibodies were investigated. One mM EDTA suppressed ADP-induced platelet aggregation by 72% and reduced force developed at 1200 s by 33%. At 234 μM, the tetrapeptide Arg-Gly-Asp-Ser (RGDS) suppressed platelet aggregation by 74%, reduced force at 1200 s by 45% and reduced gel elastic modulus by 19%. At 10 μM, the peptide D-Arg-Gly-L-Asp-L-Try (D-RGDW) completely suppressed platelet aggregation, reduced force development by 38% and reduced gel elastic modulus by 29%. At 0.133 μM, monoclonal anti-GPIIIa antibody (AP-3) reduced force development by 74% and reduced gel modulus by 60%. Murine antiGPIIb/IIIa antibodies 10E5 and 7E3 markedly suppressed force development. At 0.133 μM, 10E5 reduced force by 89% and reduced gel modulus by 67%. At 0.053 μM, 7E3 completely stopped force development and reduced gel modulus by 46%. Platelet aggregation was blocked by 0.027 μM 7E3. Selective GPIIb blockade by antibodies did not affect force development. None of the agents studied altered fibrin structure as monitored by effects on fibrin mass/length ratios. Suppression of platelet aggregation occurred at inhibitor concentrations substantially lower than those required to suppress force development. Complete suppression of platelet aggregation did not assure inhibition of clot retraction probably due to profound platelet activation by thrombin. These results indicate that inhibition of fibrin(ogen) binding to GPIIb/IIIa, either by disruption of GPIIb/IIIa or by competitive blockade, inhibits platelet mediated force development and results in clot structures which are substantially less resistant to deformation by outside forces.